How things are made. - Ajello, Arnold B.; Gibson, Barbara; National Geographic Society (U.S.). Special Publications Division ([Washington, D.C.] : National Geographic Society, 1981)
Explains how a variety of products--such as kaleidoscopes, baseballs, marbles, matches, toothpaste, light bulbs, and bridges--are made, highlighting the ways in which manufacturing techniques have changed over the years. A wall poster and a 24-page booklet of games and puzzles are included.
Prepared by the Special Publications and School Services Division; writers: Arnold B. Ajello, and others; illustrations: Barbara Gibson.
Pocket contains a pamphlet, Far-out fun (23 p.) and a poster (1 fold sheet).
Includes index.
Bibliography: p. [104]
Keywords: Manufacturing processes -- Juvenile literature; Manufactures